Uwhangchungsimwon, A Standardized Herbal Drug, Exerts an Anti-Depressive Effect in a Social Isolation Stress-Induced Mouse Model - Oh, Hyeon-Muk; Lee, Jin-Seok; Kim, Seo-Woo; Oh, Young-Taeck; Kim, Won-Yong; Lee, Sung-Bae; Cho, Yong-Rae; Jeon, Yoo-Jin; Cho, Jung-Hyo; Son, Chang-Gue (Frontiers in Pharmacology, 2020)
Introduction: Uwhangchungsimwon (UCW) is one of the most representative standardized herbal drugs for the treatment of central nervous system diseases, including mood disorders, and has been used for over 600 years in Korea and China. In spite of the long clinical application of UCW, no experimental evidence for its use against depressive disorders exists. Here, we performed an animal study to investigate the anti-depressive effect of UCW and the underlying mechanisms. Methods: A social isolation-induced depressive-like model was produced using C57BL/6J male mice by breeding the mice individually for 31 days, and the mice underwent daily oral administration of distilled water, UCW (100, 200, 400 mg/kg) or fluoxetine (20 mg/kg) during the final 17 days. A tail suspension test (TST), forced swimming test (FST) and open field test (OFT) were used to explore the effects of UCW on depressive-like behaviors. 5-Hydroxytryptamine (5-HT) was measured in the dorsal raphe nuclei (DRN) using immunofluorescence. The serum corticosterone level was measured with its receptor and catecholamine, along with cAMP response element-binding protein (CREB) and brain-derived neurotrophic factor (BDNF) in the hippocampus. Results: Social isolation stress effectively induced depressive-like behaviors, and UCW treatment significantly improved the symptoms of depressive-like behavior in the FST, TST and OFT. The isolation stress-induced depletion of 5-HT was significantly ameliorated by UCW treatment. UCW also attenuated the activation of the glucocorticoid receptor (GR) and the elevated serum corticosterone level, as well as the hippocampal levels of dopamine and norepinephrine. Dexametasone-derived translocation of GR was inhibited by UCW treatment in PC12 cells and HT22 cells. In addition, alterations of tryptophan hydroxylase 2 (TPH2), BDNF and CREB in the protein analyses were notably regulated by UCW treatment. Conclusions: These results provide animal-based evidence for the anti-depressive effect of UCW, and its underlying mechanisms may involve regulating the serotonergic system, the hypothalamic-pituitary-adrenal (HPA) axis and neurotrophin.